2021
DOI: 10.3390/polym13050751
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Flexural Behavior of Geopolymer-Based Carbon Textile/Basalt Fiber Hybrid Composite

Abstract: This paper presents an experimental research on the mechanical properties of the hybrid composite thin-plates of the short basalt fibers (CBFs)/carbon textile-reinforced geomortar. The effect of fiber contents and lengths of CBFs on the flexural behavior of carbon textile-reinforced geopolymer specimens (TRGs) was investigated by the four-point flexural strength and Charpy impact test. The experimental results of hybrid TRGs, on the one hand, were compared with reference TRGs, without CBF addition; on the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Their results indicated that the drying shrinkage of geopolymer paste decreased with increasing basalt fiber content [ 170 ]. Figure 16 shows the four-point flexural test results for basalt-fiber-reinforced geopolymers composites [ 166 ].…”
Section: Geopolymers and Natural Fiber-reinforced Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicated that the drying shrinkage of geopolymer paste decreased with increasing basalt fiber content [ 170 ]. Figure 16 shows the four-point flexural test results for basalt-fiber-reinforced geopolymers composites [ 166 ].…”
Section: Geopolymers and Natural Fiber-reinforced Compositesmentioning
confidence: 99%
“…Reprinted with permission from Refs. [ 165 , 166 ]. Copyright 2021, with permission from MDPI and Elsevier.…”
Section: Figurementioning
confidence: 99%
“…The problem with the production of these materials using additive technologies is due to the discontinuity of the material and the low tensile strength [ 41 ] and its damage can significantly reduce the dimensions of the elements produced for the construction industry [ 42 ]. Today, one of the most important research areas is the improvement bending strength of composites that would change their brittle nature of the breakthrough into ductile [ 43 ]. Currently, research is being conducted in the world on the possibility of introducing fibers as a filler into the geopolymer matrix [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Basalt fiber is one of the materials considered as reinforcement with polymer composite. The incorporation of this fiber within the polymer composite, has resulted in high operating temperature range, excellent heat, good strength, good chemical resistance, low water absorption, and good sound insulation properties [ 14 , 15 , 16 , 17 , 18 , 19 ]. Barczewski et al [ 20 ] evaluated the effect of hybridizing mineral basalt (B) powder with glass fiber in the polypropylene (PP) matrix using injection molding.…”
Section: Introductionmentioning
confidence: 99%